Activist Faith : Grassroots Women in Democratic Brazil and Chile - Drogus, Carol Ann (Book collections on Project MUSE., 2005)
An extensive and powerful literature on religion, society, and politics in Latin America in recent years has begun with the assumption that most of the movements that surged in the struggle against military rule are dead, that most of the activists are scattered and burned out, and that the promise of civil society as a source of new values and a new kind of citizenship and political life was illusory. Many have assumed that the religiously inspired activism of that period left little lasting impact, but hardly anyone has actually looked at the activists themselves to see what remains, how they cope in a different, more open environment, and how they see and act on the present and future. Activist Faith addresses these issues with a wealth of empirical detail from two key cases and with a richly interdisciplinary argument that draws on theorizing about social movements. The authors strive to understand what sustains activism and movements in radically different circumstances from those in which they arose. Their analysis is enriched by systematic attention to the impact of gender and gender-related issues on activism and movements. In the process, they shed much needed light on the fate of the activists and social movements that rose to prominence throughout Latin America during the 1980s. This beautifully written book is a major achievement that gives us analytical tools for studying how movements and activists survive in the doldrums and when a cycle of protest peaks and societies move on.-Daniel H. Levine, University of Michigan.